Answer:
A
Step-by-step explanation:
(f - g)(x)
= f(x) - g(x)
= 3x² + 4x - 6 - (6x³ - 5x² - 2) ← distribute parenthesis by - 1
= 3x² + 4x - 6 - 6x³ + 5x² + 2 ← collect like terms
= - 6x³ + 8x² + 4x - 4
Answer:
B 41.4
Step-by-step explanation:
complete Pythagoras for general triangles :
c² = a² + b² - 2ab×cos(C)
with "c" being the side opposite of the angle C.
=>
8² = 10² + 12² - 2×10×12×cos(C)
64 = 244 - 240×cos(C)
240×cos(C) = 244 - 64 = 180
cos(C) = 180/240 = 18/24 = 3/4 = 0.75
C = 41.40962211... ≈ 41.4
Answer:A
Step-by-step explanation:
3+ x/4=8
................
..